Electroless metallisation of ABS plastic: a comparative study. (2015) - Equbal, Azhar; Dixit, Nitesh Kumar; Sood, Anoop Kumar
The present work incorporates comparative evaluation between three different routes for metallisation of copper on ABS parts. These routes are aluminium paste (Al paste) coated ABS parts, chromic acid for etching of ABS part and use of H2 SO4 /H2 O2 for etching ABS parts. The main focus is to find out the best route for metallisation of ABS parts among the three routes employed. Scanning Electron Microscopy (SEM) with energy dispersive spectrometer images and electrical performance are used for comparative work. Finally, it was concluded that Al-pasted parts are best suited for metallisation of copper on them.